Multiple Doses of Icatibant used during Pregnancy - Lauren W. Kaminsky M.D.,Ph.D.; Theodore Kelbel M.D.; Fay Ansary; Timothy Craig D.O. (Allergy & Rhinology, 2017)
Background Hereditary angioedema (HAE) is a life-long disease that often manifests by puberty. Treatment of attacks is essential to improve quality of life and to decrease morbidity and mortality. During pregnancy, treatment is limited because multiple treatment options, including icatibant, are not approved for use during pregnancy. Objective We report the outcomes of three pregnancies during which icatibant was used by a patient with HAE with normal C1-inhibitor for treatment of attacks. We also reviewed the literature for reports of icatibant use during pregnancy for outcomes and adverse events. Methods We report on a patient who treated herself with icatibant during three separate pregnancies. Postpartum follow-up verified the health of the mother and children. We also performed a complete literature search of medical literature data bases on icatibant use during pregnancy. Results The patient in our report administered multiple doses of icatibant during three pregnancies. The child born from the first pregnancy and the child from the third pregnancy were born at term and without congenital anomalies. The child from the second pregnancy was 1-month preterm. All three children were developmentally normal. The literature search identified two case reports and one abstract of limited icatibant use without adverse events during pregnancy in patients with HAE. These pregnancies resulted in the births of healthy infants. Conclusion From a search of the literature, three cases of icatibant use during pregnancy resulted in healthy infants. In addition, we report that from icatibant use in three separate pregnancies, one infant was born prematurely, but there were no birth defects. From follow-up, the children continued meeting developmental milestones. This report adds to the acquisition of knowledge for drug adverse events during postmarketing surveillance for icatibant use during pregnancy.